Plan de marketing para la funeraria Carpio de la ciudad de Loja - Gálvez Carpio, María Isabel (2015)
Through this research is the general objective "PROPOSAL FOR A MARKETING PLAN FOR FUNERAL CARPIO" which allow the company to better targeting of its activities, to thereby achieve stability and permanence Funeral Carpio in the market and increase the profitability of it. Then noted in point b) is made, the summary where a review of each point of the thesis in general is done, and the results obtained throughout the investigation; in c) is the Introduction, where a contextualization of research problem and an analysis of overall shape of this work on the most important aspects, in point d) is made, has the Literature Review, where it becomes the theoretical support of this work. Here is the point e), Materials, Methods and Techniques used for the development of research as well as historical, statistical, inductive, deductive, analytical and descriptive methods were used throughout the investigation, as well as technical used as the interview applied to the Manager, the internal customer survey with a total of 20 external customers and for which a sample of 356 people who served as a source of information gathering was determined. In point f) results, a situational analysis of the CARPIO FUNERARIA, it consists of the review of the company's business philosophy, product range, current organization, the macro and micro location is in the first instance, then an external analysis based on external factors affecting the company and then an internal analysis by the interview with the manager of the company, and surveys of customers of my same of which is the matrices could be determined EFE and EFI, it is determined that the weighting factor ERA is 2.85, indicating that Funeral is exploiting the opportunities and threats that can cause a lot of damage. Regarding the weighting factor EFI, a value of 3.26 is obtained, which allows us to realize that the Funeral maintains a strong domestic position, which ensures you can go ahead and develop positively in the middle. In the high-impact matrix fo (v Strengths Opportunities), FA (v Strengths Threats), DO (v Weaknesses Opportunities) and DA (v Weaknesses Threats), they allowed raising strategies strategic objectives 4 for Funeral Carpio, on which the development of this research was cemented. g) Discussion of the proposal comprises "MARKETING PLAN FOR FUNERAL CARPIO de Loja" with the development of the objectives identified above budget was established Marketing Plan was $ 1440.60, h) are the conclusions the thesis, in which the most important are the CARPIO FUNERARIA had no mission, vision and clear goals, then it becomes known point i) Recommendations for the company is established, and within the most important a proposal for the company to present a better image because it is necessary to establish plans to offset the weaknesses and exploit internal strengths and the quality and variety of our products are made; j) k) are the Bibliography and Annexes to this investigation, and finally the index